EVALUATION OF SCHOOL BASE CURRICULUM IMPLEMENTATION (KTSP) IN PHYSICAL EDUCATION, SPORT AND HEALTH IN STATE JUNIOR HIGH SCHOOLS BANDA ACEH IN 2011 (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2012)
This study aims to: 1) know the development of Education Unit Level Curriculum (KTSP) on Physical, Sport and Health Education (Penjasorkes) subject in SMP N Banda Aceh, 2) assess whether Physical, Sport and Health Education (Penjasorkes) teachers make preparations for learning process based on the facilities and infrastructure aspect, 3) determine whether teachers implement the learning process of Physical, Sport and Health Education (Penjasorkes) based on standard process, 4) determine the learning result of Physical, Sport and Health Education (Penjasorkes) achieved by students.The type of this research is a program evaluation research. The approach used was CIPP model in terms of stages of Context, Input, Process, and Product. The populations in this study were state Junior High Schools in Banda Aceh. The samples in this study were school principals and Physical, Sport and Health Education (Penjasorkes) teachers. The research data was taken using interview, observation, and documentation technique. And, data analysis in this study was descriptive analysis.The results of this study showed that stage of context, human resources aspects: 1) teachers understanding about curriculum, from 19 schools, 74% are good and 26% were still lacking. 2) the application of Education Unit Level Curriculum (KTSP), 74% from 19 schools have been implemented well and 26% are still lacking. Aspects of government and community support: 1) government support, from 19 schools, 63% are good and 37% are still lacking. 2) public support of 19 schools, 5% are good and 95% are still lacking. Phase of facilities and infrastructure aspects: 1) the availability of facilities and infrastructure, from 19 schools, 47% had good facilities and infrastructure and 53% are still lacking. 2) the feasibility of facilities and infrastructure, from 19 schools, 47% are good and 53% are still lacking. Aspects of teaching materials development: 1) making the the curriculum device, from 19 schools, 53% are good and 47% are still lacking. 2) creating a model of learning, from 19 schools, 74% are good and 26% are still lacking. Stage of process, aspects of curriculum implementation: 1) implementation of the curriculum, from 19 schools, 84% are good and 16% are still lacking. 2) constraints in the application of Education Unit Level Curriculum (KTSP), from 19 schools, 47% do not have constraints and 53% still have constraints. Product stage, aspects of learning outcomes: 1) the success of curriculum implementation, from 19 schools, 95% are good and 5% is still lacking. 2) the implementation of curriculum of 19 schools, 58% are good and 42% are still lacking.Based on the findings of this research, the suggestions can be delivered to the principals and supervisors so that they pay more attention to the teachers in implementing Physical, Sport and Health Education (Penjasorkes) curriculum so the expectation in curriculum development can be achieved well. The principals and supervisors should give guidance to the teachers to develop the Physical, Sport and Health Education (Penjasorkes) curriculum so that the device used is appropriate with learning process. Teachers are expected to be able to create models of learning so that students are more active in learning process. In the implementation of learning process, teachers are expected to implement learning process based on standard process. The implementation of Education Unit Level Curriculum (KTSP) is quite satisfactory, but teachers are expected to increase achievement in sports field.